Daily Intake of Wheat Germ-Enriched Bread May Promote a Healthy Gut Bacterial Microbiota: a Randomised Controlled Trial - Moreira-Rosário, A (2022)
Purpose: Wheat bran fibre has a beneficial effect on gastrointestinal function, but evidence for wheat germ is scarce. Accordingly, we evaluated the effects of daily intake of wheat germ on gastrointestinal discomfort and gut microbiota by adding wheat germ to refined (white) wheat bread, the most consumed bread type. We hypothesised that an improvement in the composition of refined bread could beneficially affect intestinal health without compromising consumers' acceptance. Methods: Fifty-five healthy adults were recruited for a randomised, double-blind, crossover, controlled trial comprising two 4-week intervention periods separated by a 5-week washout stage. During the first 4-week period, one group consumed wheat bread enriched with 6 g of wheat germ and the control group consumed non-enriched wheat bread. Results: Wheat germ-enriched bread was well-appreciated and the number of participants that demonstrated minimal gastrointestinal improvements after wheat-germ intake was higher than in the control arm. Importantly, intake of wheat germ-enriched bread decreased the perceived gastrointestinal discomfort-related quality of life (subscale worries and concerns) over refined white bread. The improvements in the gastrointestinal function were accompanied by favourable changes in gut microbiota, increasing the number of Bacteroides spp. and Bifidobacterium spp. Conclusions: Adding wheat germ to industrially made white bread without altering sensory properties may promote a healthy gut bacterial microbiota and the gastrointestinal health.